Direito comunitário: o processo de integração latino-americano e seu paradigma europeu - Franco, René Alejandro Enrique Farias (2007)
This work we have the pleasure to present to the illustrious members of this distinguished examining body are due to the teachings transmitted by the eminent teachers from this Dignified House of Superior Studies: Celso Ribeiro Bastos, Cláudio Finkelstein, Paulo de Barros Carvalho, Renan Lotufo, Marcelo de Oliveira Santos, Jacy de Souza Mendonça, Heleno Torres e Walter Douglas Stuber, enriched by the discussions and comments made in class, as well as by the researches made during the studying years, involving extra courses and academic activities under the scientific and operational scope given the communitarian law basis. The principle of this work results from the analyses of the historical attempts of integration among the Latin American Nations, especially concerning the formation of commercial and political integration blocks, which attempted the emerging of a new law branch: Communitarian Law . This work does not have as a goal the specific integration law operations, though a macro-legal study of this new legal science, endeavoring in its sources the historical wealth of the integral people involved in the integration process, assigned with the constitution of efficient rules for conquering their objectives. The European Union, The Southern Common Market, the Andean Pact and the recent tries to make feasible The Free Trade Area of the Americas (FTAA), parallel to the new Latin American leadership focused on the integration of their people - undoubtedly the greatest milestone from the beginning of this Millennium, thus, enriching the theme by itself, justifying the research in this historical and revolutionary social-judicial context. Nothing could be better than the comparative studies of the evolution of the European Union Communitarian Law compared to the juridical advances of the Southern Common Market and The Andean Community. Summarizing, a study of the meetings and problems inherent to their present transitory era